2000
DOI: 10.1053/euhj.1999.1875
|View full text |Cite
|
Sign up to set email alerts
|

Depressed low frequency power of heart rate variability as an independent predictor of sudden death in chronic heart failure

Abstract: Depressed heart rate variability has independent prognostic value in patients with chronic heart failure; spectral analysis identifies an increased risk for sudden death in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
160
4
13

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 253 publications
(185 citation statements)
references
References 35 publications
8
160
4
13
Order By: Relevance
“…Decreased M 2 R expression has been previously reported in left ventricular hypertrophy or chronic heart failure, two situations associated with an increased risk of cardiovascular mortality. 25,26 Similar changes have been described in a canine model of dietary-induced obesity 17 and, following analysis of their heart rates, it has been suggested that these changes could also occur in obese patients. 27 In vivo studies assessing cardiac muscarinic receptivity are limited by confounding factors such as interactions between various circulating agents (leptin, free fatty acids) and insulin.…”
Section: Discussionmentioning
confidence: 72%
“…Decreased M 2 R expression has been previously reported in left ventricular hypertrophy or chronic heart failure, two situations associated with an increased risk of cardiovascular mortality. 25,26 Similar changes have been described in a canine model of dietary-induced obesity 17 and, following analysis of their heart rates, it has been suggested that these changes could also occur in obese patients. 27 In vivo studies assessing cardiac muscarinic receptivity are limited by confounding factors such as interactions between various circulating agents (leptin, free fatty acids) and insulin.…”
Section: Discussionmentioning
confidence: 72%
“…Several parameters that describe heart rate behaviour have been attributed to the risk for sudden cardiac death in postinfarction and chronic heart failure patients (Galinier et al 2000;La Rovere et al 2003;Guzzetti et al 2005;Mäkikallio et al 2005). However, the definitions of sudden death in follow-up studies lack the specificity for sudden arrhythmic death .…”
Section: Prediction Of Sudden Cardiac Death By Measurement Of Hrv/dynmentioning
confidence: 99%
“…17 However, both increased 18 and reduced 5 LF power were found to be associated with an increased risk of cardiac death. Recent data from Galinier et al 7 showed that reduced daytime LF power from 24-hour Holter recording independently and significantly predicted sudden death, although very few other parameters were included in the analysis.…”
Section: Prognostic Value Of Hrv In Chf Patientsmentioning
confidence: 99%